Detection of pathogenic variants in Alzheimer's disease related genes in Bulgarian patients by pooled whole-exome sequencing. Issue 1 (31st December 2023) - Karachanak-Yankova, Sena; Serbezov, Dimitar; Mihaylova, Marta; Nikolova, Dragomira; Balabanski, Lubomir; Damyanova, Vera; Antonova, Olga; Staneva, Rada; Ganev, Mihail; Spasova, Victoria; Rukova, Blaga; Nesheva, Desislava; et al.
Abstract: In an effort to better understand the complex genetic background of Alzheimer's disease (AD) we performed high-coverage whole-exome sequencing of a DNA pool assembled of 66 Bulgarian AD patients. We focused our analysis on genes demonstrated to have association with AD in previous studies, i.e. PSEN1, PSEN2, APP, APOE, TREM2, HFE, CLU and CR1 . In these genes, we established six pathogenic/likely pathogenic variants in the sequenced pool, three common and three rare. Two of these variants showed statically non-significant difference between Bulgarian AD patients and Bulgarian control exomes, the hemochromatosis variant rs104894002 ( HFE ) and rs7412 ( APOE ), which, notwithstanding its pathogenicity score, has putative protective role against AD. Three of the remaining four pathogenic/likely pathogenic variants were estimated to significantly differ in frequency between the analyzed AD patient pool and controls. These are the rs429358 ( APOE ) polymorphism, a well-established risk factor for Alzheimer's disease, the rs28936380 ( PSEN2 ) and rs104894002 ( TREM2 ), also ascertained to be associated with AD. The performed study validates the role of three pathogenic/likely pathogenic variants in AD related genes in the multifaceted genetic etiology of Alzheimer's disease.